BOOK REVIEW Visual Thinking Strategies in Montessori Environments - Broome, John (Journal of Montessori Research, 2022)
Using almost 30 years of research, the National Center for Montessori in the Public Sector (NCMPS) and Philip Yenawine present the case for visual thinking strategies (VTS) as an opportunity to apply these strategies in the Montessori learning environment by centering engagement with art. The overall goal of VTS is to provide an accessible transformative learning experience through an open-ended discussion of visual art that increases a student’s literacy, language, and critical thinking skills.